Tear Here: the Impact of Object Transformations on Proper Disposal - Baxter,W; Aurisicchio,M; Childs,PRN (2016)
Efforts promoting proper disposal of packaging generally focus on infrastructure and messaging. Significantly less attention has been given to how the attributes of packaging can be used to change disposal behaviour. This research shows how changes in packaging attributes (e.g. alterations in shape, colour, or size) influence two disposal behaviours: recycling and littering. Specifically, we use an implicit association test to measure the subconscious tendency to categorize altered objects as trash rather than recycling. The results indicate that 82% or respondents showed at least a slight effect and 53% showed a strong effect towards associating altered objects with waste. Next, we evaluate object transformations on littering behaviour through an observational field study. Observations (N = 2823) indicated that littering is influenced by deformed, torn, disassembled, and partially full packaging. No significant effect was found with regard to packaging that is wet, sticky, has undergone colour changes or that is has remains (e.g. sauce) on it. These findings suggest that the (re)design of packaging can significantly influence proper disposal. Based on this, packaging can be (re)designed in two ways. First, many types of packaging have scripted alterations such as the iconic ‘tear here’ indicator. These can be changed to preserve properties associated with recyclables and non-littering. Second, packaging can be designed so that there are fewer alterations during use. This work can also help identify inherent attributes that encourage proper disposal.